Long-term outcomes of the micronet-covered stent system routine use for carotid revsacularization in stroke prevention: PARADIGM-Extend 5 year evidence. (25th November 2020) - Mazurek, A; Borratynska, A; Tomaszewski, T; Lesniak-Sobelga, A; Wilkolek, P; Gancarczyk, U; Brozda, M; Sobieraj, E; Sikorska, M; Czyz, L; Urbanczyk, M; Trystula, M; et al.
Abstract: Background: Diffusion-weighted magnetic resonance imaging indicates that micronet-covered embolic prevention stent system effectively minimizes peri-procedural and prevents lesion-related post-procedural cerebral embolism in carotid artery stenting but long-term clinical evidence is missing. Purpose: To provide long-term clinical and duplex ultrasound evaluation of safety and efficacy of the system use in consecutive carotid revascularization patients. Methods: PARADIGM-EXTEND is in all-comer, all-referrals-tracked study with no exclusion criteria other than lack of NeuroVascular Team-determined indication. Clinically asymptomatic patients receive revascularization only in case of increased-stroke-risk characteristics. Adverse events are independently adjudicated. Results: Currently 451 patients (48–87 years, 59% symptomatic, 127 women) with 490 arteries crossed the first follow-up window of 30 days. There has been 100% micronet-covered embolic prevention stent system use (ie, no other stent type/s used throughout study). Proximal/distal intra-procedural neuroprotection use was 38.3%/61.7%. Large balloon/high-pressure stent optimization was routine, leading to a single-digit (mean 6.9%) residual diameter stenosis. Independent neurologist and duplex evaluation are before and after revascularization (48h and 30 days, then yearly). Peri-procedural death or major ischemic stroke rate was 0%. One event (prior infarct scar asymptomatic extension in prolonged hypotension course) was adjudicated as minor stroke (0.22%), and there was 1 periprocedural MI (type 2, in 2-vessel non-revascularizable CTO; 0.22%). By 30 days there were no further ischaemic strokes (0%) but there was 1 haemorrhagic transformation that led to death (0.22%) and 1 bleeding-related death (0.22%). Thus total 30-day death/stroke was 0.66%, and total death/stroke/MI was 0.88%. By 60 months there were 3 contralateral, 1 ipsilateral (device-unrelated), and 2 posterior circulation strokes. Baseline internal carotid artery velocities were 3.72±1.25 and 0.63±0.69 m/s (peak-systolic and end-diastolic). Post-procedural in-stent velocities were normal and remained normal throughout the 60-month follow-up period: 0.78±040 and 0.21±0.10 (1y); 0.75±0.36 0.19±0.09 (2y); 0.75±0, 35 and 0.21±0.09 (3y); 0.72±0.27 and 0.20±0.07 (4y); 0.79±0.58 and 0.21±0.11m/s (5y). There were 2 in-stent restenoses by 1y (including 1 that occurred with de novo neck radiotherapy) and 1 other by 2y (total 2y in-stent restenosis of 1.1%) but no further ones (0% in-stent restenosis at 2–5y). Conclusions: PARADIGM-Extend long-term clinical and duplex ultrasound evidence is consistent with normal healing and sustained safety and stroke prevention efficacy of the micronet-covered embolic prevention stent system used routinely, on top of optimized medical therapy, for stroke prevention in symptomatic and increased-stroke-risk asymptomatic subjects with carotid stenosis recommended for revasularization by the NeuroVascular Team. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Jagiellonian University Medical College